MAULANA SYAIKH TGKH. M. ZAINUDDIN ABDUL MADJID’S QURANIC ASPECTS: A Systematic Literature Review - Salim, Salim Rahmatullah; Mohd. Shafiee bin Hamzah (UIN Mataram, 2022)
Tuan guru Kyai Haji Muhammad Zainuddin Abdul Madjid (HAMZANWADI), a Sasaknese, preacher, educator, and an Indonesian national hero, is the prominent ulama. He contributed to numerous Islamic life and movement aspects. Conversely, limited studies identify his Quranic aspects. This study aims to explain HAMZANWADI`s Quranic aspects. It is a Qualitative study that uses document analysis and focuses on the articles relating to HAMZANWADI published from 2015 to 2021. This analysis is conducted to know the trend of HAMZANWADI in literature. This research applies for a systematic literature review and uses it as a principle methodological tool. It also adopts the technique of PRISMA. The findings elucidate that HAMZANWADI is frequently researched in his works. The education theme is HAMZANWADI`s trend in literature. No specific studies makes his quranic side as the main focus. Conversely, three studies uncover a little quranic side of HAMZANWADI: first, discussing the relevancy of character education’s value in Wasiat Renungan Masa with the Quran. Second, the political concepts of HAMZANWADI referred to the Quran. Third, observing the education system of Ma’had Darul Quran Walhadis. This study is important to show the need of research on the Quranic aspect of HAMZANWADI due to limited studies in it.